THE ROLE OF BRAND IMAGE IN BUILDING BRAND LOYALTY IN BHS BRAND COVERS - Asiyah, Siti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research is motivated by the lack of research on Muslim clothing, especially BHS brand sarongs. In fact, this research can increase the sales turnover of the sarong industry in Indonesia. Apart from that, this research aims to examine the role of brand image in building brand loyalty and brand trust. In this research, brand image is predicted to have the power to build brand loyalty and brand trust. This research aims to test and analyze the behavior of BHS sarong consumers in the cities of Malang and Pasuruan. The data in this study were analyzed using SEM SmartPLS 2.0. The sampling method used is a non-probability sampling method, with a purposive sampling technique. The number of respondents used reached 100 people. The findings of this research are that brand image is able to increase brand loyalty from BHS sarongs. However, brand trust is not able to mediate the relationship between brand image and brand loyalty, because to form brand loyalty, consumers also need purchasing power.